Cost‐effective design and evaluation of wireless sensor networks using topology‐planning methods in small‐world context. Issue 2 (1st June 2014) - Tadayon, Navid; Zonouz, Amir Ehsani; Aïssa, Sonia; Xing, Liudong
Abstract : Low‐power consumption and network resiliency are among the vital qualities for having a seamless, quality‐oriented wireless communication. Networks with small‐world property are known to possess both these favourable qualities. However, wireless networks are not inherently small‐world, neither is easy and cost‐effective to artificially create networks with this property by using the existing techniques. In other words, the traditional blind rewiring techniques that aimed at enhancing the network with such features, suffer from inefficiency and saturation behaviour. In this study, the authors propose topology‐planning methods that efficiently exploit the expensive long‐reach transmission facilities to add the small‐world property to the network. The authors show that these methods are practical, cost‐effective and efficient since they are appropriately tailored based upon the network realities, such as topology and channel fading. The proposed methods are tested for networks with diverse ranges of 'clustering coefficient' and 'diameter' in order to prove their aptitudes in dealing with real situations. The results illustrate that the incorporation of these techniques altogether decreases the network 'diameter' by almost 50% and the 'average path length' by 47%. This corresponds to 67% less facilities compared with blind rewiring techniques.